Child Rights Education for Inclusion and Protection Primary Prevention - Desai, Murli (Rights-based Direct Practice with Children,, 2018)
The aims of child rights education are to make children and their primary duty-bearers aware of child rights so that they both can be empowered to together advocate for and apply them at their family, school and community levels. This sourcebook focuses on child rights education for primary prevention related to inclusion and protection. Child rights education for exclusion, non-discrimination and inclusion is discussed in the context of family and society with reference to girls, children with disability, and Dalit and tribal children, and child rights to cultural and financial inclusion. Child rights education for protection comprises prevention of violence against children with reference to physical abuse/ corporal punishment and bullying, commercial exploitation of children with reference to child labour and trafficking and sale of children, sexual abuse and exploitation of children, problems in adolescent sexual relationships such as violence, teenage pregnancy, abortion and unwed motherhood, and sexually transmitted infections and HIV, child marriage, and conflict with law. This is a necessary read for social workers, lawyers, researchers, trainers and teachers working on child rights across the world, and especially in developing countries. .